16th and 17th centuries lead glazes from Carnide (Lisbon) - Casimiro, Tânia Manuel (2019)
Lead glazes, brown, yellow or green, are frequently found in Early Modern contexts associated to kitchen ware, although usually corresponding to no more than a small percentage of the total assemblages. While 16th and 17th century potters’ regulations mention which forms were produced and how they should be manufactured, cook books from that same period determine the use of such wares in preparing, cooking and serving food. The collection found in Carnide, just outside Lisbon, as the filling of hundreds of deactivated storages pits may shed some light on the use of these ceramics in domestic environments and their importance in everyday activities.